PENGARUH PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) DAN KEPUASAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA (Studi Kasus di Badan Keuangan Daerah Kota Batu) - Veni Rikusita; Ronny Malavia Mardani; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract  This study aims at finding out: 1)the effect of TPP (additional income for civil servant) on performance of Civil Servant in Badan Keuangan Daerah Kota Batu, 2) the effect of work satisfaction on performance of civil servant of Badan Keuangan Daerah Kota Batu. This study employs quantitative explanatory method by using descriptive approach. The writer selects Badan Keuangan Daerah Kota Batu as location of study where there are 110 civil servants. Data gathered by using questionnaire of likert scale. Data analysis consists of  requirements test such as validity, reliability and normality test and t test as well as multiple linear regression test. This findings of this study shows that: 1) TPP has significant effect on performance of civil servant of Badan Keuangan Daerah Kota Batu, 2) work satisfaction has significant effect on performance of civil servant of Badan Keuangan Daerah Kota Batu, 3) simultaneously, TPP and work satisfaction has significant effect on performance of civil servant of Badan Keuangan Daerah Kota Batu.  Keywords: Performance of civil servant, TPP and work satisfaction